2021
DOI: 10.3389/fmolb.2021.684866
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of circRNA circ_0001666 Represses EMT in Pancreatic Cancer Through Upregulating miR-1251 and Downregulating SOX4

Abstract: BackgroundPancreatic cancer (PC) is an aggressive malignancy and has a poor prognosis. Although emerging research has revealed that circular RNAs (circRNAs) are crucial modulators that control tumor development and metastasis, their functional involvement in PC has not been well characterized. Here, we examined whether and how circRNA circ_0001666 governs epithelial-mesenchymal transition (EMT) in PC.MethodsWe investigated the effects of circ_0001666 on EMT and PC cell invasion by gain- and loss-of-function as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Next, the magnetic beads were incubated with proteinase K buffer for 30 min. Finally, the enrichment of HUMT, miR-455-5p, and LRP4 in purified RNAs was examined by qRT-PCR [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Next, the magnetic beads were incubated with proteinase K buffer for 30 min. Finally, the enrichment of HUMT, miR-455-5p, and LRP4 in purified RNAs was examined by qRT-PCR [ 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…Given the highly metastatic nature of pancreatic cancer cells, distant metastasis, especially lymphatic metastasis, occurs in the early stage of pancreatic cancer. Relevant studies have shown that high expression of circ0074298, circCCT3, and circ0001666 in pancreatic cancer is closely related to lymph node metastasis (93)(94)(95), while low expression of circNFIB1 and circ0092367 is related to advanced TNM stage, lymph node metastasis, and overall survival (96,97). High expression of circZNF91 promotes chemotherapy resistance in pancreatic cancer cells and is inversely proportional to overall survival (98).…”
Section: Pancreatic Cancermentioning
confidence: 99%
“…Similarly, Zhang et al demonstrated that overexpression of circ0001666 leads to low expression of E-cadherin and upregulation of Vimentin, and promotes EMT in pancreatic cancer cells. Mechanistically, circ0001666 acts as a sponge for miR-1251 to weaken the inhibition of miR-1251 on the downstream target SOX4, and the high expression of SOX4 in turn regulates the EMT of cancer cells by upregulating the expression of EZH2 and promoting the invasive properties of pancreatic cancer cells (94). Xu et al reported that HepG2 and Huh7 cells overexpressing miR-145 had increased expression of E-cadherin and reduced expression of N-cadherin, leading to reduced migration and invasion abilities.…”
Section: Circrna Induces Emt and Tumor Cell Migrationmentioning
confidence: 99%
“…circ-0001666 (chr6:170,626,457-170,639,638) overexpression in PDAC increases transcription factor SOX4 expression, a direct downstream effector of miR-1251 , by binding to miR-1251 ( Zhang et al, 2021 ). Silencing circ-0001666 repressed EMT in PDAC cells by upregulating miR-1251 and downregulating SOX4 ( Zhang et al, 2021 ). This study indicated that circ-0001666 functions via a ceRNA mechanism.…”
Section: Circular Rnas In Pdacmentioning
confidence: 99%